PERAN KURIKULUM MERDEKA SEBAGAI UPAYA GURU DALAM MENGATASI LEARNING LOSS DI KELAS 4 SD NEGERI SERANG 3 - Zerlina, Fadhiilah Taaj; Andriana, Encep; Setiawan, Sigit (STKIP Persada Khatulistiwa Sintang, 2025)
The phenomenon of learning loss occurred both before and during the pandemic, resulting in the decline of students’ general and specific knowledge and skills. In response, the government introduced the Merdeka Curriculum, which is expected to address the challenges and limitations found in the previous curriculum. Therefore, teachers are required to develop effective strategies to implement the Merdeka Curriculum and overcome learning loss. This study aims to describe the role of the Merdeka Curriculum as a teacher’s effort to address learning loss in Grade IV A of SD Negeri Serang 3. The research employed a descriptive qualitative method with the class teacher of Grade IV A as the research subject. Data were collected through interviews, observation, and documentation, and analyzed using an interactive analysis model consisting of data collection, data reduction, and data verification. The results showed that the teacher’s strategies included deepening understanding of the Merdeka Curriculum by seeking information and preparing lesson plans involving models, methods, and learning media—one of which was implementing differentiated learning. Challenges during the pandemic included limited internet access, data quota issues, and low parental involvement. The Merdeka Curriculum proved effective in mitigating learning loss by promoting active student participation, critical thinking, and creativity through the Projek Penguatan Profil Pelajar Pancasila (P5).